The Effectiveness of Ta'zir in Increasing Discipline of Santri at the boarding school: The Effectiveness of Ta'zir in Increasing Discipline of Santri at the boarding school - Mohammad Saat Ibnu Waqfin (SCHOOLAR: Social and Literature Study in Education, 2025)
The development of Islamic education in Indonesia has never been separated from the historical aspects behind the process of entering and developing Islamic education in Indonesia. Historically, Islamic education was most studied and developed in Islamic boarding schools. Islamic boarding school is an Islamic religious educational institution that is growing and recognized by the surrounding community, which also plays a role as an institution for religious guidance, science, training, community development and at the same time being a cultural node. Usually these roles are not immediately formed but go through stage by stage, program by program. After being successful as an educational institution, Islamic boarding schools can also become scientific, training and community empowerment institutions. Its success in building integration with society gave it a mandate as an institution for religious guidance and a cultural node. Referring to the aim of education in Islamic boarding schools in developing individual (santri) behavior, namely in this case the issue of discipline, according to Sahertian is to build behavior and develop individual potential and create a harmonious life and produce results in group processes. Effective discipline allows a person with his activities to fulfill the basic need to be together. In order to achieve the goals mentioned above, students must be equipped with Islamic values. This is realized through the rules and regulations enforced by the Islamic boarding school. By enforcing these regulations, the students have high discipline so they can achieve the predetermined goals. Because filling and equipping students' cognitive abilities is only a small part of the goals of education.